Cambrian stratigraphy of the Tomten-1 drill core, Västergötland, Sweden. (1st October 2016) - Ahlberg, Per; Eriksson, Mats E.; Lundberg, Frans; Lindskog, Anders
Abstract: The Tomten-1 drilling at Torbjörntorp in Västergötland, southern Sweden, penetrated 29.85 m of Cambrian Series 2, Cambrian Series 3, Furongian, and Lower–Middle Ordovician strata. Lithostratigraphically, the succession includes the File Haidar, Borgholm and Alum Shale formations, and the Latorp and Lanna limestones. The drill core succession is described herein for the first time, with special focus on the biostratigraphy of the Cambrian Alum Shale Formation. In the Cambrian Series 3, through Furongian Alum Shale Formation, agnostoids and trilobites have been identified to species level and the succession is subdivided into nine biozones (in ascending order): the Ptychagnostus gibbus, Ptychagnostus atavus, Lejopyge laevigata, Agnostus pisiformis, Olenus gibbosus, Parabolina spinulosa, Ctenopyge tumida, Ctenopyge bisulcata and Ctenopyge linnarssoni zones. The succession is interrupted by numerous stratigraphic gaps of variable magnitudes, as is evident from the biostratigraphy and conspicuous unconformities.